From Merkel Cell Polyomavirus Infection to Merkel Cell Carcinoma Oncogenesis - Krump, Nathan A.; You, Jianxin (Frontiers in Microbiology, 2021)
Merkel cell polyomavirus (MCPyV) infection causes near-ubiquitous, asymptomatic infection in the skin, but occasionally leads to an aggressive skin cancer called Merkel cell carcinoma (MCC). Epidemiological evidence suggests that poorly controlled MCPyV infection may be a precursor to MCPyV-associated MCC. Clearer understanding of host responses that normally control MCPyV infection could inform prophylactic measures in at-risk groups. Similarly, the presence of MCPyV in most MCCs could imbue them with vulnerabilities that-if better characterized-could yield targeted intervention solutions for metastatic MCC cases. In this review, we discuss recent developments in elucidating the interplay between host cells and MCPyV within the context of viral infection and MCC oncogenesis. We also propose a model in which insufficient restriction of MCPyV infection in aging and chronically UV-damaged skin causes unbridled viral replication that licenses MCC tumorigenesis.